USING YOUTUBE AS UNLIMITED EDUCATIONAL VIDEO RESOURCES IN TEACHING ENGLISH SKILLS - Muchtar Naely; Laundung Alimin; Halim Shanty; Nisa Khairun (Institut Agama Islam Negeri Palopo, 2015)
The video site YouTube can be a valuable tool to teach English and arouse learner independence. Using YouTube both inside and outside the classroom can improve conversation, listening and pronunciation skills. YouTube video can also be utilized as regalia to enhance exposure to the world and support authentic vocabulary development. If students and teachers/lecturers have unlimited access to the Internet, YouTube can be a useful tool through which multiple skills in English can be taught. This paper offered possible inadequacy that may come by using online video technology.